Novel ceramic membranes for gas separation in enabling the clean energy delivery - Zhang, Chi (Curtin University, 2016)
Ceramic membranes have wide applications in clean energy delivery and greener chemical synthesis. However, the prerequisite to realize such potentials is the membranes to possess sufficiently high CO2-resistance. In this thesis, a series of novel oxygen selective ceramic ion-conducting membranes with high stability have been theoretically and experimentally investigated via the strategies including element doping, short circuit design and membrane surface decoration. The developed membranes display very high stability in CO2-containing atmosphere at high temperatures.